2015
DOI: 10.1038/srep12857
|View full text |Cite
|
Sign up to set email alerts
|

CACUL1/CAC1 Regulates the Antioxidant Response by Stabilizing Nrf2

Abstract: Nrf2 is the pre-dominant transcription activator responsible for coordinated up-regulation of ARE-driven antioxidant and detoxification genes. The activity of Nrf2 is tightly regulated at basal levels through its ubiquitination by Cul3-Keap1 and consequential degradation. Upon exposure to stress, the Cul3-Keap1 ligase is inhibited, leading to Nrf2 stabilization and activation. Here we describe CACUL1/CAC1 as a positive regulator of the Nrf2 pathway. We found that CACUL1 is up-regulated by Nrf2-activating oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Our previous studies found that Helicobacter and deoxycholic acid could promote the expression of CACUL1 and promote the proliferation and metastasis of tumor cells [20][21][22]. Our study also found that CACUL1 was highly expressed in GBC.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Our previous studies found that Helicobacter and deoxycholic acid could promote the expression of CACUL1 and promote the proliferation and metastasis of tumor cells [20][21][22]. Our study also found that CACUL1 was highly expressed in GBC.…”
supporting
confidence: 74%
“…The activity of Nrf2 was tightly regulated at basal levels through its ubiquitination by Cul3-Keap1 and consequential degradation. Upon exposure to stress, the Cul3-Keap1 ligase is inhibited by CACUL1, leading to Nrf2 stabilization and activation [21]. Therefore, we speculated that CACUL1 promotes ITGBL1 expression through NRF2.…”
Section: Cacul1 Upregulated the Expression Of Itgbl1 Through Nrf2mentioning
confidence: 97%
“…How other candidates contributes to senescence will be our future interest. Cacul1 was found to down-regulate p53 transcriptional activity, regulation oxidative pressure and apoptosis (Kong et al, 2013;Kigoshi et al, 2015;Fukuda et al, 2017), which suggest Cacul1 may act as a suppress factor in cell aging process. Trdmt1 plays an important role in tRNA methylation to prevent tRNA cleavage into fragment, thus stabilize overall translation (Ghanbarian et al, 2016;Jeltsch et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that CAC1 knockdown might lead to increased cellular stress response and p53 protein expression [17]. In another study, CAC1 was suggested as the positive regulator of Nrf2 in cell survival [12].…”
Section: Discussionmentioning
confidence: 99%
“…CDK2-associated cullin domain 1 (CAC1) is mapped to chromosome 10 in humans (10q35-36, Gene Bank accession number AY743663) [11], and is classified as a cullin domain-containing protein and a member of the cullin family of E3 ubiquitin ligases [12]. It has been shown that CAC1 promotes cell cycle progression and activates cyclin-dependent kinase 2 (CDK2) kinase activity via multiple extracellular signals, including growth factors, mitogens, deoxycholic acid (DCA), curcumin, and even chemotherapy drugs [13, 14].…”
Section: Introductionmentioning
confidence: 99%